Vibrio parahaemolyticus-specific Halobacteriovorax From Seawater of a Mussel Harvesting Area in the Adriatic Sea: Abundance, Diversity, Efficiency and Relationship With the Prey Natural Level - Ottaviani, Donatella; Pieralisi, Silvia; Rocchegiani, Elena; Latini, Mario; Leoni, Francesca; Mosca, Francesco; Pallavicini, Alberto; Tiscar, Pietro Giorgio; Angelico, Gabriele (Frontiers in Microbiology, 2020)
This research aimed to study the abundance and molecular diversity of V. parahaemolyticus-specific Halobacteriovorax strains isolated from seawater of Adriatic sea and relationship between predator and prey abundances. Moreover, predator efficiency of the Halobacteriovorax isolates towards V. parahaemolyticus and V.cholerae non-O1/O139 strains was tested. V.parahaemolyticus NCTC 10885 was used as primary host for the isolation of Halobacteriovorax from seawater by the plaque assay. Molecular identification was performed by PCR detection of a fragment of the 16S rRNA gene of the Halobacteriovoraceae family members. Moreover, 700 bp PCR products were sequenced and compared between them and to clones described for other sampling sites. Vibrio counts were performed on TCBS agar from 100 ml of filtered water samples and presumptive colonies were confirmed by standard methods. Predatory efficiency of Halobacteriovorax isolates was tested by monitoring abilities of three-day enrichments to form clear lytic halos on a lawn of Vibrio preys, by the plaque assay. Out of 12 seawater samples monthly collected from June 2017 and May 2018, 10 were positive for V.parahaemolyticus specific Halobacteriovorax with counts ranging from 4 to 1.4 x 103 PFU per 7.5 ml. No significant relationship was found between Halobacteriovorax and Vibrio abundances. The 16SrRNA sequences, one for each positive sample, were divided into 3 clusters. Within the clusters, some sequences had 100% similarity. Some sequences also clustered with other sequences submitted to GenBank and belonged to strains of different origin. All Halobacteriovorax isolates had the ability to prey all tested Vibrio strains. Additional research is necessary to assess whether stable strains of Halobacteriovorax are present in Adriatic Sea and to understand the mechanisms by which Halobacteriovorax may modulate abundance of V.parahaemolyticus and other vibrios in a complex marine ecosystem.